2004
DOI: 10.1002/ca.10187
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the pelvic plexus and innervation of the prostate gland

Abstract: We have examined the anatomy of the pelvic (inferior hypogastric) plexus in six male cadavers, paying particular attention to gross anatomical landmarks that might aid in locating it and have used immunohistochemistry to study the small branches of the plexus that supply the prostate gland. The pelvic plexus was found two finger breadths lateral to the third anterior sacral foramina, lying deep to a line drawn from third sacral vertebra, the conventional level of the recto-sigmoid junction, and the palpable po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…It is delimited cranially by the rectovesical pouch of Douglas. The septum rectovesicale, extending in a coronal plane, divides the space into a retrovesical or retroprostatic space, anteriorly, and into a prerectal space, posteriorly (Diop et al, 2003;Ali et al, 2004;Venuti et al, 2004;Standring et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It is delimited cranially by the rectovesical pouch of Douglas. The septum rectovesicale, extending in a coronal plane, divides the space into a retrovesical or retroprostatic space, anteriorly, and into a prerectal space, posteriorly (Diop et al, 2003;Ali et al, 2004;Venuti et al, 2004;Standring et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical studies, in contrast, are more feasible and could help guide subsequent functional studies. We previously showed that the position of the inferior hypogastric plexus can be located consistently in the cadaver with the use of surgical landmarks [17]. The present study builds upon these observations determine the extent to which the fascia containing the fine branches of this plexus can be put under tension by the movement of pelvic organs.…”
Section: Introductionmentioning
confidence: 52%
“…The position of the plexus in the endopelvic fascia was taken as two fingers breadth lateral to the third anterior sacral foramina, lying deep to a line drawn from the thirds sacral vertebra, the conventional level of the rectosigmoid junction, and the palpable posterior surface of the pubic symphysis [17]. Taking care to remain superficial to the endopelvic fascia, a note was made of the relations of this fascia and the ease with which displacement of this fascia could be produced by gentle movement of related visceral structures to an extent that was considered to reflect the range possible during life.…”
Section: Methodsmentioning
confidence: 99%
“…In male mammals, PP (similarly as indicated above in females) extends caudally on both sides of the rectum and reaches the border of the vas deferens and seminal vesicles (Tsaknakis 1971). However, in males of large mammals PP comprises of one large ganglion called the anterior pelvic ganglion (APG) and several smaller in size ganglia scattered throughout the plexus (Kaleczyc et al 2003a, Ali et al 2004. In males and females of rodents, the structure of PP is even more simplified since in animal species such as the rat, guinea-pig or mouse one large major pelvic ganglion (MPG) and only a few small accessory pelvic ganglia are present (Dhami and Mitchell 1991, Mitchell 1993, Keast 1995, Wanigasekara et al 2003.…”
Section: Introductionmentioning
confidence: 91%